2015
DOI: 10.1521/bumc.2015.79.1.41
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the construct of earned security in adolescents: Evidence from an inpatient sample

Abstract: In adult attachment research, a group of individuals who convey secure attachments despite recalling difficult early caregiver relationships has been identified. The term earned security refers to individuals in this group, whereas continuous security refers to individuals who convey secure attachments and describe caring early relationships. Evidence on the validity of earned security in adults is mixed--with one longitudinal study showing that earned secure adults, despite contrary recollections, are actuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 28 publications
(60 reference statements)
0
1
0
2
Order By: Relevance
“…On the contrary, they argued that attachment insecurity may be only one pathway among several to psychopathology and that it is not a necessary precondition to psychopathology, although it is quite a common occurrence. Regarding this issue, a fascinating study (Venta et al, 2015b) investigated the construct of earned attachment security (Pearson et al, 1994) in a sample of 240 inpatient adolescents. They found that 19 (8%) adolescents who were assigned to the secure CAI classification reported negative experiences with their mothers on the care subscale of the Parental Bonding Inventory (PBI; Parker et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, they argued that attachment insecurity may be only one pathway among several to psychopathology and that it is not a necessary precondition to psychopathology, although it is quite a common occurrence. Regarding this issue, a fascinating study (Venta et al, 2015b) investigated the construct of earned attachment security (Pearson et al, 1994) in a sample of 240 inpatient adolescents. They found that 19 (8%) adolescents who were assigned to the secure CAI classification reported negative experiences with their mothers on the care subscale of the Parental Bonding Inventory (PBI; Parker et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Sedangkan, attachment related -anxiety, sebenarnya memiliki keinginan yang besar untuk membangun sebuah hubungan dan sebenarnya membutuhkan suatu bentuk hubungan yang memberikan kedekatan dan perlindungan, tetapi dalam konteks ini hal tersebut memiliki kekhawatiran dalam kehadiran pasangannya. (Venta, Sharp, Shmueli-Goetz, & Newlin, 2015). Individu akan menjalani pemulihan attachment ketika pengalaman memiliki insecure attachment dilihat sebagai suatu hal yang koheren, yaitu suatu bagian dari kehidupannya.…”
Section: Pendahuluanunclassified
“…Individu akan menjalani pemulihan attachment ketika pengalaman memiliki insecure attachment dilihat sebagai suatu hal yang koheren, yaitu suatu bagian dari kehidupannya. Hal tersebut juga didukung dengan jangka waktu pemulihan dan sosok signifikan lain yang membantu proses individu dalam memeroleh secure attachment (Venta, Sharp, Shmueli-Goetz, & Newlin, 2015).…”
Section: Pendahuluanunclassified
“…After this publication, researchers lost interest in earning security, and recently it has been discussed only in case studies ( Guina, 2016 ) or qualitative research ( Dansby Olufowote et al, 2020 ). However, Venta et al (2015) noted that the non-longitudinal nature of changes in attachment should not put the study of the earned secure group to an end. Defining our focus is crucial: is it external reality, where childhood neglect might not have occurred, or mental reality, where an individual recalls inadequate care, impacting their functioning, regardless of facts?…”
Section: Introductionmentioning
confidence: 99%
“…A particular internal reorganization most likely occurred and allowed an individual to benefit from a good internal relationship despite negative evaluation of care early in life. Understanding how this group differs from those with consistent subjective experiences (e.g., low childhood care and insecure adult attachment, or optimal childhood care and secure adult attachment) is important, given the widespread nature of this inconsistency (8-20% of the general population; see Roisman et al, 2002 ; Saunders et al, 2011 ; Venta et al, 2015 ). Addressing these concerns, Venta et al (2015) proposed replacing “earned secure” with “negative recall subtype of secure attachment”, which does not imply change over a lifetime.…”
Section: Introductionmentioning
confidence: 99%